Contextualização da pesca mundial de lagostas e características de comercialização de Scyllarides spp. e Panulirus spp. na Baixada Santista, Estado de São Paulo, Brasil - Duarte, Luis Felipe de Almeida [UNESP]; Severino-Rodrigues, Evandro; Gasalla, Maria de Los Angeles (My University, 2011)
This study aimed to contextualize the world's lobster fishing and identify the characteristics of their trades in Santos region (SP). For this purpose, were realized surveys about the captures of 56 years referring the families traded in the world through the informations supplied by the FAO (Food and Agriculture Organization). To State of São Paulo, consults were made in the data base Propesq (Fishing Institute) about the fishing and prices. Besides interviews in fishmonger, businessmen of fishing and restaurant, we observed the trade and the economical potential compared the lobsters Scyllarides spp. and Panulirus spp. The worldwide the family Nephropidae is the one that has been presenting bigger growth in the captures from 1950 and the one that has the biggest observed captures, the Palinuridae showed a little growth of the captures up to the 80' years, and leaving from there it is oscillating without many expressive changes; Scyllarides began to stand out as fisheries only 70' in Asia, precisely where the other two Families had low catches proportional. In the State of São Paulo, two types of lobsters are sold in Baixada Santista, with conspicuous differences in prices between them. There is also a difference in the flow of trade in relation to active fishing gear. Traders notice a decrease in both abundance and size of individuals of both genders and a clear preference to sell the slippers lobsters (Scyllarides spp.) both for the quality of meat as the lowest price.
Contextualization of world fisheries lobsters and trade characteristics of Scyllarides spp. and Panulirus spp. in Baixada Santista, São Paulo State, Brazil
Keywords: Panulirus; Scyllarides; Slipper lobster; Trade